Refining multiple ontologies: A mappings-based approach - Lu, Jianjiang; Xu, Baowen; Wang, Peng; Kang, Dazhou; Zhou, Jin (INFOCOMP Journal of Computer Science, 2005)
In a distributed environment like Semantic Web, complex applications often need to handle multiple ontologies, where the heterogeneity of multiple ontologies arises. In order to reconcile these ontologies, ontology mappings are proposed to provide the interoperating rules between multiple ontologies. However, introducing mappings may cause inconsistencies and redundancies, which will break the soundness and balance of the original ontologies. This paper proposes an approach to eliminate inconsistencies and redundancies. First the mappings are classified into eleven kinds and multiple ontologies are modeled as a graph. Then the changes of the graph, when introducing different kinds of mappings orderly, are analyzed. Following refining steps include semantic checking to keep multiple ontologies sound, and semantic refinement to avoid multiple redundancies. All the steps in our approach can be performed in polynomial time. Our method has high efficiency and is feasible to applications about multiple ontologies in a distributed environment.